Association of Lumbar Spondylolytic Spondylolisthesis With the Incidence and Prognosis of Anterior Ring Apophyseal Abnormalities of the Vertebrae in Young Gymnasts. Issue 1 (10th January 2023) - Urushibara, Makoto; Kawasaki, Takayuki; Aihara, Takato; Kojima, Atsushi
Background: Although anterior apophyseal abnormalities of the vertebrae and spondylolytic spondylolisthesis (SS) are prevalent in gymnasts during growth spurts, no studies have examined the relationship between apophyseal abnormalities and SS. Hypothesis: A significant relationship will exist between anterior apophyseal abnormalities and SS in young gymnasts. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 306 gymnasts (123 male, 183 female; age range, 6-28 years) with >2 weeks of back pain were enrolled in this study. Apophyseal abnormalities were evaluated using radiography. In the primary analysis, multiple logistic regression analysis was performed to assess the odds ratio (OR) for multivariate factors (age, body mass index, sex, skeletal maturity, competitive level, and presence of spondylolysis or SS) influencing the incidence of apophyseal abnormalities. In the secondary analysis, 90 of the 306 gymnasts were followed up radiographically for a minimum of 2 years, and factors contributing to the worsening of apophyseal abnormalities were identified. Results: In the primary analysis, the chi-square test revealed a relationship between anterior ring apophyseal abnormalities and SS at the L5-S1 segment (OR, 7.6). Multiple logistic regression analysis demonstrated that the presence of SS at L5-S1 (OR, 9.5) and competitive level (international: OR, 6.7; national: OR, 4.5) correlated with the incidence of apophyseal abnormalities. The secondary analysis identified the presence of SS at L5-S1 (OR, 5.9) as a significant factor contributing to the worsening of apophyseal abnormalities. Conclusion: The presence of SS was a factor affecting the incidence and prognosis of anterior apophyseal abnormalities.